2019
DOI: 10.1142/s2424786319500191
|View full text |Cite
|
Sign up to set email alerts
|

Does bank capital affect the monetary policy transmission mechanism? A case study of Emerging Market Economies (EMEs)

Abstract: The objective of this study is to investigate the impact of bank capital on monetary policy transmission mechanism during the period from 2010 to 2016 for 20 Emerging Market Economics (EMEs) by using the two-step system generalized method of moments (GMM). The coefficient of excess capital in low-asset countries is found to be negative which reveals the importance of excess capital for the effectiveness of monetary transmission. However, the study could not find the significance of excess capital for high-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The study found that external debt adversely affects economic growth. Abbas et al (2019), in a study on emerging economies on a data set of six years from Pakistan, found that excess capital is good for an economy. This association is more relevant to low assets countries since high asset countries have other options to generate income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that external debt adversely affects economic growth. Abbas et al (2019), in a study on emerging economies on a data set of six years from Pakistan, found that excess capital is good for an economy. This association is more relevant to low assets countries since high asset countries have other options to generate income.…”
Section: Literature Reviewmentioning
confidence: 99%